Role of estuarine natural processes in removal of trace metals under emergency situations - A.R. Karbassi; S. Tajziehchi; N. Farhang Adib (Global Journal of Environmental Science and Management)
Estuaries are well known for their potential in removing metal from fresh water to provide micro-nutrients to aquatic life. In the present investigation, we have tried to bring out the metal removal potential of estuaries during accidental spills. For this purpose artificial river water containing high concentration of Mn, Cu, Zn, Ni and Pb were mixed with sea water at different salinity regimes. Water samples were taken from a station on the main branch of Tajan River that flows in to the Caspian Sea. For this purpose, solutions with a concentration of 5 mg/L of each studied metal (Mn,Cu, Zn, Pb) were prepared in Tajan River water. The salinity regimes include 3, 6, 8, 10 and 11 ppt. It was noted that metal concentration decreased by increasing salinity. Metals were flocculated at different rates: Cu (88%) > Ni (86%) > Pb (84%) > Mn (74%).Thus, as average about 80% of total elemental content flocculates. Hence, it was concluded that a large amount of micro nutrients is carried by the river and flocculated in the estuary where the river water mixes with the sea water which may play a vital role in supplying nutrients to the aquatic animals. Cluster analyses have shown that Mn and Ni are governed by EC, pH and salinity.